Aesthetics, Disinterestedness, and Effectiveness in Political Art - Asavei, Maria Alina (Lexington Books, 2018)
Should politically concerned and engaged artistic production disregard questions or/and requirements of aesthetic reception and value? Whether art should be “aesthetic” or “political” is not a new question. Therefore, in spite of those several contemporary approaches of this issue, the answer is not set in stone and the debate is still going on. This volume aims to broaden these debates and it stems from numerous conversations with politically engaged artists and artist collectives on issues related to the “aesthetitzation of politics” versus the “politicization of art,” as well as the phenomenon of the so-called “unhealthy aestheticism” in political art. Thus, this study has three interrelated aims: Firstly, it aims to offer an interdisciplinary account of the relationship between art and politics and between aesthetics and the political. Secondly, it attempts to explore what exactly makes artistic production a strong – yet neglected – field of political critique when democratic political agency, history from below and identity politics are threatened. Finally, to illuminate the relationship between critical political theory, on the one hand, and the philosophy of art, on the other by highlighting artworks’ moral, political and epistemic abilities to reveal, criticize, problematize and intervene politically in our political reality.